Public Attention and Digital Financial Inclusion in Indonesia: Google Trends Evidence on QRIS and Digital Public Service Infrastructure - PUTRI, REZA ANGGIDYA; Kayla Putri, Reviana; Fitri, Safira; Suci Ramadhani, Alya Ayu; Nur Azizah, Adinda; Noer Habibah, Adiva Alfi; Frila Ardianti, Maeva; Hasanah , Uswatun (Kampus 5 Universitas Negeri Surabaya, 2026)
The rapid expansion of digital payment systems has become a central element of monetary and financial sector reforms in emerging economies. In Indonesia, the implementation of the Quick Response Code Indonesian Standard (QRIS) aims to enhance payment system efficiency, interoperability, and financial inclusion. However, the effectiveness of such reforms depends not only on infrastructure availability but also on public awareness and information-seeking behaviour, which typically precede actual adoption and sustained usage. This study examines whether online search intensity can serve as a high-frequency indicator of public attention toward digital payment infrastructure in Indonesia. Using monthly Google Trends data from January 2023 to December 2025, the analysis focuses on search interest in “QRIS” as the primary variable, with “Layanan Online” and “Smart City” included as contextual benchmarks representing broader digitalisation narratives. A time-series–oriented approach is employed, incorporating stationarity testing, first differencing, and correlation as well as lead–lag analysis to examine the dynamics of public attention. The findings indicate that changes in public attention to QRIS display distinct temporal patterns and exhibit meaningful dynamic relationships with attention to online services, suggesting that shifts in attention to digital payments may precede broader engagement with digital public services. These results support the interpretation of search-based indicators as early signals of behavioural readiness for digital payment adoption. From a policy perspective, the study highlights the usefulness of high-frequency attention data for monitoring payment system reforms and informing communication strategies to support digital financial inclusion Keywords: Digital payments; QRIS; Financial inclusion; Google Trends; Public attention